Jeśli masz bibliotekę i kota,masz wszystko, czego potrzebujesz = If You Have a Library and a Cat, You Have Everything You Need - Hołyst, Katarzyna (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
A modern library should be a welcoming, open institution for everyone, integrating the community, providing a platform for development and activity, and serving as a space where tradition meets modernity?drawing from the history, people, and the place in which it operates. It should provide access to culture and knowledge while functioning as a hub of social life. The library in Drezdenko strives to meet these expectations, but to fulfill its mission as effectively as possible, proper technical support and promotional engagement are essential. The article describes the transformation process of the Ks. J. Tischner Public Library of the Town and Municipality of Drezdenko into a modern, friendly library, creating the city's cultural and promotional centre.
Keywords: modernizacja; biblioteka; przestrzeń; oferta; kultura; edukacja; promocja; modernisation; library; space; offers; culture; education; promotion